PROGRAM PENGEMBANGAN KEWIRAUSAHAAN (PPK) UNIVERSITAS AHMAD DAHLAN [ENTREPRENEURSHIP DEVELOPMENT PROGRAM OF UNIVERSITAS AHMAD DAHLAN] - Ahmad Rizal Solihudin; Hendro Setyono; Hari Haryadi (Jurnal Sinergitas PKM & CSR, 2019)
Entrepreneurship Develeopment Program (Pengembangan Kewirausahaan - PPK) at Universitas Ahmad Dahlan (UAD) aims to produce entrepreneurs who come from UAD students and alumni. This program is expected to produce new entrepreneurs with information technology as competitive advantage. The design of PPK UAD used Experiental Learning Method (ELM). This approach broadly gives treatment to students to get the experience, competence and basic character of entrepreneurs. This program is carried out by UAD lecturers and involves business practitioners and other institutions as well as the business community outside Universitas Ahmad Dahlan. Business practitioner partnets come from the financial, food, creative and information technology industries. The program also involved several business communities in Yogyakarta such as the Muhammadiyah and JCI Network. The implementation of PPK UAD includes management training and business expertise for tenants, especially in mastering IT business model and e commerce. In addition, internship to companies is also held as a benchmark of industry of each tenant. Tenants also receive business assistance and marketing facilities. PPK UAD activities in 2018 were followed by 20 tenants which were selected from 43 registrants. Tenant comes from PKM students, active students who pioneered new businesses and alumni. PPK UAD 2018 resulted in 5 new entrepreneur graduates ready to run the business. This new entrepreneur consists of 2 tenants who are very prepared with competitive advantages and 3 tenants who are ready to start new businesses.Bahasa Indonesia Abstrak: Program Pengembangan Kewirausahaan (PPK) di Universitas Ahmad Dahlan (UAD) bertujuan mencetak wirausaha yang berasal dari kalangan mahasiswa dan alumni UAD berbasis information technology (IT). Program ini diharapkan dapat menghasilkan wirausaha baru dengan teknologi informasi sebagai basis competitive advantage. Desain pelaksanaan PPK UAD menggunakan pendekatan metode Experimental Learning (EL). Pendekatan ini secara garis besar memberi treatment kepada mahasiswa untuk mendapat pengalaman, kompetensi dan karakter dasar entrepreneur. Program ini dilaksanakan oleh dosen UAD serta melibatkan praktisi bisnis dan institusi lain serta komunitas bisnis di luar Universitas Ahmad Dahlan. Praktisi bisnis berasal dari industri keuangan, pangan, kreatif dan teknologi informasi. Selain itu, kegiatan ini juga melibatkan beberapa komunitas bisnis di Yogyakarta seperti Jaringan Saudagar Muhammadiyah dan JCI. Aplikasi nyata dari PPK UAD antara lain berbentuk pelatihan manajemen dan keahlian bisnis bagi tenant terutama dalam penguasaan sistem business model dan pemasaran berbasis IT.  Selain itu, diadakan pula pemagangan pada perusahaan yang menjadi benchmark pada industri masing-masing tenant. Tenant juga mendapat pendampingan usaha dan fasilitas pemasaran produk. Kegiatan PPK UAD tahun 2018 diikuti 20 tenant yang merupakan hasil seleksi dari 43 pendaftar. Tenant berasal dari kalangan mahasiswa PKM, mahasiswa aktif yang merintis usaha baru serta alumni. Program Pengembangan Kewirausahan PPK UAD tahun 2018 menghasilkan 5 lulusan wirausahawan baru yang siap menjalankan bisnis. Wirausahawan baru ini terdiri dari 2 tenant yang sangat siap dengan competitive advantage dan 3 tenant yang siap merintis usaha baru.Kata kunci: Kewirausahaan, Inkubasi Bisnis, Competitive Advantage, Information Technology